Peran Pemerintah Desa Rendeng dalam Pengembangan Desa Wisata Edukasi Gerabah di Desa Rendeng, Kecamatan Malo, Kabupaten Bojonegoro - Aquatama, Rio Pradana; Karsidi , Ravik; Kartono, Drajat Tri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The purpose of this study is to analyze the role of village government in the development of Pottery Education Tourism Village in Rendeng Village, Malo District, Bojonegoro Regency. Analyzing the supporting factors of the village government's role in the development of Pottery Education Tourism Village in Rendeng Village, Malo District, Bojonegoro Regency.The researcher's research methods are qualitative and quantitative. In this study, researchers used qualitative data types. This type of qualitative data is a type of data in the form of descriptive and in-depth words and actions about an event. This data contains an analysis of the current condition of the institution related to the research raised so as to help researchers determine the problem. Conclusion From the results The role of the village government in providing support, can be seen from the coaching and training carried out to improve community skills. Despite all the roles carried out by the Rendeng Village Government as a supporter, overall this role cannot be said to be maximal.   Supporting factors for the role of the village government in the development of the first tourism village, namely the Bojonegoro Regency Government and related agencies support the Rendeng Village Government in carrying out its role as a social animation by carrying out village development assistance, as well as paving the way for village cooperation and partnership).